(untitled) (Quest Journal of Management and Social Sciences, 2020)
Background: The transition in the education system was parallel to the humankind and the technological revolution has been increasing issues in the education system around the globe. The shift in education system tends to understand how learning styles of students affect education quality with completely different forms of e-learning. Education 4.0 tackles society’s desire in the ’innovative age’. Such education training will demonstrate the ability of the learner to use the latest technology to help the learner adapt as per the changes in society. Students in education 4.0 become more self-reliant in their own education, pressuring educators to accept a new function as administrators who might influence the learners across their education process. This paper aims to explore pandemic as a driver of enhancement of Education 4.0 in Nepal in terms of school level technology change. The paper applies the thorough review of the literature on Education 4.0 in wider perspective as well as in Nepalese context. Objective: This paper aims to analyze the enhancement of education 4.0 in Nepal in terms of review from school level technology change. Results: It is observed that education 4.0 is a very necessary reform in the education system in Nepal. The major need of the time is the upliftment of the education sector from the traditional ones and makes the implementation of education 4.0. It helps in the improvement of digital competencies in all level, and the use of digital technologies for teaching and learning. The research regarding the changes in the education system has been conducted in various nations around the globe. Conclusions: It is found that the learners mostly prefer those technology with whom they are more familiar such as use audio/video conferencing technologies rather than any other tools. Education revolution is not an easy task for the developing countries as there is a lack of local research regarding the new technologies in educational sectors. Nepal has tremendous opportunities to drastically reform education in an offer to address deep structural inequalities. Originality: This paper is original and not published anywhere else.